A new species of the genus Biemna Gray, 1867 (Porifera: Biemnidae) from shallow waters of the Northwestern Iberian coasts - Cristobo, Javier; Almón, Bruno; Pérez, Jacinto; Ríos, Pilar (Zootaxa, 2024)
The genus Biemna currently includes fifty-eight valid species distributed worldwide with a wide depth range. In this paper, we describe a new species of this genus, Biemna begonae sp. nov., collected by scuba diving in two different locations on the Galician coast (NW Spain). The typical skeleton of this group is composed by megascleres arranged in a plumose or plumoreticulate fashion, with ectosomal skeleton constituted by brushes of choanosomal tracts and microscleres, including sigmata, commata and raphides. The habitus of the new species is a hemispherical cushion-shaped with numerous tubular projections emerging from the base, ending in oscules, and a general burgundy-red or whitish cream colour in live specimens. Spicules are styles, rare rhabdostyles, four size classes of sigmata, and raphides. The new species is compared morphologically with the other European representatives of the genus.